Six-Minute Walk, Maximal Exercise Tests: Reproducibility in Fibrotic Interstitial Pneumonia - Eaton, Tam; Young, Pam; Milne, David; Wells, Athol U (American journal of respiratory and critical care medicine, 2005)
Resting pulmonary function and exercise variables are widely used to stage and monitor idiopathic interstitial pneumonia (IIP). However, the variability of exercise data (maximal exercise and the 6-minute walk test) has not been evaluated definitively. We have prospectively quantified the reproducibility of resting and exercise functional data in fibrotic IIP (idiopathic pulmonary fibrosis, fibrotic nonspecific interstitial pneumonia) and have evaluated interrelationships between variables. Thirty consecutive patients with fibrotic IIP underwent serial resting pulmonary function tests, 6-minute walk (n = 29), and maximal exercise (n = 24) at an interval of 1 week, with all testing performed in accordance with American Thoracic Society standards. Within-subject reproducibility was excellent for 6-minute walk distance (SD/mean = 4.2%) and clinically acceptable for resting pulmonary function indices and VO(2)max on maximal exercise testing. However, the amplitude of oxygen desaturation at the end of exercise was poorly reproducible in both 6-minute walk and maximal exercise testing (SD/mean > 25%). There was a highly significant relationship between VO2max on maximal exercise testing and 6-minute walk distance (r(s) = 0.78, p < 0.0001). In fibrotic IIP, the excellent reproducibility of the 6-minute walk distance is a major advantage in routine staging and monitoring, whereas maximal exercise variables are poorly reproducible.